The relationship between schedule flexibility and domain-specific satisfaction via work-to-family enrichment for working parents in South Africa - Giuricich, Daniela Adriana (Organisational Psychology, 2016)
Employees discretion over the scheduling of their work hours, often referred to as schedule flexibility, has been repeatedly linked to increases in both job satisfaction and family satisfaction. Despite the international research, evidence on these relationships has not been empirically tested in the South African context. There is also a gap in understanding the role of perceived work-to-family enrichment on the relationship between schedule flexibility and domain-specific satisfaction. To address these gaps in our knowledge, this study investigated the relationship between schedule flexibility and domain-specific satisfaction amongst South African employees, and assessed the role of work-to-family enrichment as a mediator of this relationship. Work-to-family enrichment occurs when a resource gain in the work domain promotes gains in the family domain. The propositions were tested among working parents that used schedule flexibility (N= 121) across multiple organisations in South Africa. Working parents responded to a self-report online survey. The questionnaire contained, inter alia, measures of schedule flexibility use, schedule flexibility availability, work-to-family enrichment, job satisfaction, family satisfaction and personal demographics. Correlation and regression analysis were used to test the propositions. Preacher and Hayes' (2004) PROCESS script was used to test mediation effects. The results of the analyses indicated that there is a significant positive and proportional relationship between the use of schedule flexibility and domain-specific satisfaction. The use of schedule flexibility was more strongly correlated to job satisfaction than employee knowledge regarding the availability of schedule flexibility in the organisation. Further analysis showed that work-to-family enrichment mediated the relationship between schedule flexibility use and domain-specific satisfaction.